Metode Interpretasi Hukum Aplikasi Dalam Hukum Keluarga Islam Dan Ekonomi Syariah - Al Amin, Muhammad Nur Kholis; Abdullah, Agung; Santoso, Fattah Setiawan; Muthmainnah, Muthmainnah; Sembodo, Cipto (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2023)
This research aims to explain the importance of interpretation of the law — to the formulation of legal texts that already have legal certainty — for a law enforcement officer who aims to maintain the value of justice and the usefulness of the law, especially in the realm of Islamic family law and Syariah Economics. So that the judge as law enforcement who in the speech is considered to know the law (ius curia novit) is able to solve the problems that enter based on certainty, justice, and legal expediency. This is then made a subject matter as an interesting study of what is the method of interpretation as part of the method of legal discovery, besides that there is also the relevance of the ijitihad method as one way in the interpretation of law to the application of Islamic family law and Syariah Economics. This research is a literature study that tries to describe the importance of interpretation of legal texts (laws and regulations) through descriptive-analysis methods that process data qualitatively, so as to generate answers about the importance of legal interpretation and examples of its application in Islamic family law and Syariah Economics.